Factors Affecting Profit Quality With Company Size as a Moderating Variable - Huda, Nurul; Muhsin, Muhsin; Kurniawan, Rudi; Espa, Vitriyan; Rusmita, Sari (STMIK Widya Cipta Dharma, 2025)
This study aims to analyze the factors that influence earnings quality with company size as a moderating variable at Regional Development Banks (BPD) in Indonesia during the period 2019-2023. The factors tested in this study include capital structure, profitability, and liquidity. This study uses a quantitative method with a moderated regression approach. The data used are secondary data obtained from the annual financial reports of BPDs registered during the study period. The research sample was obtained through a purposive sampling technique, with a final sample size of 110 observations. The results of the study indicate that capital structure, profitability, and liquidity have a significant effect on earnings quality. An optimal capital structure can improve earnings quality, while high profitability indicates a better internal control system and more transparent accounting practices. In addition, companies with high liquidity have better financial flexibility, so they can avoid financial pressure and reduce the potential for earnings manipulation. Moderation analysis shows that company size is able to moderate the effect of capital structure and liquidity on earnings quality, but does not moderate the effect of profitability on earnings quality.